2020
DOI: 10.21203/rs.2.20616/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioural plasticity of Anopheles coluzzii and Anopheles arabiensis undermines LLIN community protective effect in a Sudanese-savannah village in Burkina Faso

Abstract: Background: Despite the overall major impact of Long Lasting Insecticide treated Nets (LLINs) in eliciting individual and collective protection to malaria infections, some sub-Saharan Countries, including Burkina Faso, still carry a disproportionately high share of the global malaria burden. This study aims to analyse the possible entomological bases of LLIN limited impact, focusing on a LLIN-protected village in the Plateau Central region of Burkina Faso. Methods: Human Landing Catches (HLCs) were carried out… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…Differently from the previously quoted study in the South-western region of the country (42), a limited insecticidal pressure derived from insecticide use against agricultural pest is expected in the present study site. In addition, our study site has been characterized entomologically for over ten years, supporting the results here retrieved with other parameters related with vector response to ITN pressure (45)(46)(47)(48).…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Differently from the previously quoted study in the South-western region of the country (42), a limited insecticidal pressure derived from insecticide use against agricultural pest is expected in the present study site. In addition, our study site has been characterized entomologically for over ten years, supporting the results here retrieved with other parameters related with vector response to ITN pressure (45)(46)(47)(48).…”
Section: Introductionsupporting
confidence: 87%
“…Mosquitoes analysed in the context of the current study were part of larger entomological collections conducted in years 2011, 2015 and 2020 (45,47,48). Brie y, in 2011 indoor and outdoor resting collections were carried out by pyrethrum spray catches and sticky resting box, while in 2015 and 2020 host seeking mosquitoes were collected inside and outside houses by human landing catches.…”
Section: Entomological Collections and Specimen Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral plasticity of An. arabiensis has been shown to compromise the protective effects of ITNs, as they bite both indoors and outdoors throughout the night (Perugini et al, 2020). Several studies conducted in western Kenya have reported insecticide resistance in An.…”
Section: Introductionmentioning
confidence: 99%
“…coluzzii evolution across the continent (6,7). The adaptive flexibility of this mosquito has been also highlighted by its rapid competence to expand its range of peak biting times in order to avoid insecticide treated bed-nets (8). This extraordinary adaptative capacity makes this malaria vector a threat for malaria control.…”
Section: Introductionmentioning
confidence: 99%